Expression profiling and functional characterization of selected oil palm genes in host-microbial interaction - Tan, Yung Chie (2013)
Basal stem rot is a major disease of oil palm caused by a pathogenic fungus,Ganoderma boninense. It reduces the oil palm yield and causes severe economic loss to the oil palm industry. To better understand oil palm defence system during the host-pathogenic interactions, the gene expression profiles of eleven defence-related cDNAs in oil palm treated with G. boninense, Trichoderma harzianum, or mycorrhizas were studied. These cDNAs encode putative bowman-birk serine protease inhibitors (EgBBI1 and 2), defensin (EgDFS), dehydrin (EgDHN), early methionine labelled polypeptides (EgEMLP1 and 2), glycine rich RNA binding protein (EgGRRBP), isoflavone reductase (EgIFR), metallothionein-like protein (EgMT), pathogenesis-related protein-1 (EgPRP), and type 2 ribosome inactivating protein (EgT2RIP). These cDNAs were chosen because they are related to plant defence and were differentially expressed in oil palm upon inoculation by mycorrhizas or G. boninensen in a previous study. In this study, the transcript abundance of EgIFR and EgBBI2 increased in G. boninense-treated roots at 3 and/or 6 weeks post inoculation (wpi). While the gene expression of EgT2RIP, EgBBI1, and EgDFS increased in G. boninense-treated roots at 6 and/or 12 wpi. Meanwhile, EgDHN was up-regulated at all three time points. These reveal that these genes could have different roles at different stages during the infection. Transcript profiles in leaves showed two candidate genes encoding EgEMLP1 and EgMT with different profiles in G. boninense-treated leaves compared to that of T. harzianum. They may have the potential to be developed as biomarkers for early detection of G. boninense infection. Comparison of the transcripts expression profiles in the roots inoculated by G.boninense, T. harzianum, and mycorrhizas showed that some of the transcripts were increased by specific fungi (EgBBI1 and EgMT were up-regulated by G.boninense while EgPRP was up-regulated by mycorrhizas). However, EgDFS and EgT2RIP were up-regulated by all three fungi probably as a result of plant general defence mechanism. The putative functions of these cDNAs were identified by sequence analyses with other homologous proteins. SignalP predicted that EgBBI1 and 2 , EgDFS, EgPRP, and EgT2RIP are secretory proteins. The complete open reading frames (ORFs) of EgBBI1, EgDFS, EgIFR, EgPRP, and EgT2RIP were cloned for recombinant protein production. EgDFSm, EgT2RIPm-CA, and EgT2RIPm-CB were sub-cloned after removal of signal peptide and linker peptide sequences. Soluble recombinant proteins were obtained for EgDFSm, EgIFR,EgT2RIPm-CA while partially soluble protein was obtained for EgT2RIPm-CB. The recombinant EgDFSm managed to inhibit the growth of G. boninense mycelium by inhibiting the assimilation of starch, possibly by acting on α-amylase or calcium channel of the fungus. The butanol fraction of oil palm root extract treated with EgIFR showed some differences in its chemical profiles when analysed using a reverse-phase-high performance liquid chromatography (RP-HPLC). Lastly, the recombinant EgT2RIPm-CA and CB that formed EgT2RIPm-AB was found to be toxic to both mammalian cell lines, MCF-7 and MCF-10. In conclusion, the findings of this study have provided insights on the molecular events that happened during the plant-microbe interaction as well as functional roles of some proteins encoded by these cDNAs.